Organoids from colorectal peritoneal metastases as a platform for improving hyperthermic intraperitoneal chemotherapy. Issue 10 (14th June 2019) - Ubink, I; Bolhaqueiro, A C F; Elias, S G; Raats, D A E; Constantinides, A; Peters, N A; Wassenaar, E C E; de Hingh, I H J T; Rovers, K P; van Grevenstein, W M U; Laclé, M M; Kops, G J P L; et al.
Abstract: Background: Patients with peritoneal metastases from colorectal cancer have a poor prognosis. If the intraperitoneal tumour load is limited, patients may be eligible for cytoreductive surgery followed by hyperthermic intraperitoneal chemotherapy (HIPEC). This treatment has improved overall survival, but recurrence rates are high. The aim of this study was to create a preclinical platform for the development of more effective intraperitoneal chemotherapy strategies. Methods: Using organoid technology, five tumour cultures were generated from malignant ascites and resected peritoneal metastases. These were used in an in vitro HIPEC model to assess sensitivity to mitomycin C (MMC) and oxaliplatin, the drugs used most commonly in HIPEC. The model was also used to test a rational combination treatment involving MMC and inhibitors of the checkpoint kinase ATR. Results: MMC was more effective in eliminating peritoneal metastasis-derived organoids than oxaliplatin at clinically relevant concentrations. However, the drug concentrations required to eliminate 50 per cent of the tumour cells (IC50) were higher than the median clinical dose in two of five organoid lines for MMC, and all five lines for oxaliplatin, indicating a general resistance to monotherapy. ATR inhibition increased the sensitivity of all peritoneal metastasis-derived organoids to MMC, as the IC50 decreased 2·6–12·4-fold to well below concentrations commonly attained in clinical practice. Live-cell imaging and flow cytometric analysis showed that ATR inhibition did not release cells from MMC-induced cell cycle arrest, but caused increased replication stress and accelerated cell death. Conclusion: Peritoneal metastasis-derived organoids can be used to evaluate existing HIPEC regimens on an individual-patient level and for development of more effective treatment strategies. Surgical relevance Cytoreductive surgery followed by hyperthermic intraperitoneal chemotherapy (HIPEC) has improved prognosis of patients with peritoneal metastases from colorectal cancer, but disease recurrence is common. More effective and personalized HIPEC is urgently needed. Organoid technology is frequently used for drug screens, as patient-derived organoids can accurately predict clinical therapeutic response in vitro . A panel of organoids was established from peritoneal metastases from colorectal cancer and used to develop a model for testing HIPEC regimens in vitro . Patient-derived organoids differed in sensitivity to commonly used chemotherapeutics, in line with variable clinical outcomes following cytoreductive surgery–HIPEC. Combining MMC with an ATR inhibitor improved the efficacy of MMC. Peritoneal metastasis-derived organoids can be used as a platform to test novel (combination) strategies that increase HIPEC efficacy. In the future, organoids could be used to select patent-tailored HIPEC regimens. Graphical Abstract: Organoid technology was used to create a preclinical model for evaluation of hyperthermic intraperitoneal chemotherapy (HIPEC) for peritoneal metastases from colorectal cancer. Current HIPEC regimens were tested and a novel rational treatment combination of mitomycin C with inhibitors of ATR was investigated. This combination improved HIPEC efficacy and has potential for clinical implementation. Exciting advances